Dinamika Penegakan Hukum dan Demokrasi di Indonesia: Perspektif Historis, Sosial-Politik, dan Konstitusional - Claragista Intan Asriani; Asyam, Muhammad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Indonesia as a country of law and democracy has a solid foundation in Pancasila and the 1945 Constitution of the Republic of Indonesia. The dynamics of law enforcement and democracy in Indonesia are inseparable from the influence of historical,socio-political, and cultural factors that shape the course of the national legal system. This study uses the literature review method to examine the results of related studies, which show that aw enforcement in Indonesia faces various challenges, ranging fro legal pluralis, structural injustice, to political influence and technological developments in the digital era. Indonesian democracy is rooted in the values of Pancasila which demand social justice, respect for human rights, unity, and deliberation. However, in enforcement is still often hampered by corruption, weak integrity of legal complexity in a multicultural society.